Thermal Properties of Geopolymers with Silica Fume. Issue 1 (January 2020) - Sampe, Fanriyanto; Triwiyono, Andreas; Ayu Agustini, Ni Komang; Perdana, Indra
Abstract: Fly ash-based geopolymer is a renewable technology to minimize the use of cement in the construction field. The development was not only the use of fly ash but also the addition of other materials such as silica fume to geopolymer paste. Insulating materials is one of the examples of fly ash-based geopolymer applications. This paper examines the influence of varied activating solution of fly ash ratio and silica fume on the behavior of thermal properties of the geopolymer paste. The activating solution of fly ash ratio (A/F) was 40%, 45%, and 50%. Silica fume acts as a substitution of fly ash varied from 1%, 2%, and 4%. The activating solution was mixed with NaOH 10 M and Na2 SiO3 with Na2 SiO3 /NaOH ratio constant at 2. Geopolymer paste was subjected to different tests such as thermal conductivity, bulk density, and compressive strength. The results showed that the geopolymer paste with substitution of silica fume had thermal conductivity, bulk density and compressive strength in the range of 0.051 to 0.932 W/m.C, 1752.457 to 1870.309 kg/m 3 and 25.41 to 38.48 MPa respectively. The thermal conductivity values for all variations are below 1 W/m.C. Results from this work shows that the mixture suitable as a thermal insulation material.